How ideas are born : illustrators on creative processes / Miguel Ángel Arteaga. - Pérez Arteaga, Miguel Á. (Miguel Ángel), 1965- (Hoaki, 2023)
An insightful and visually rich book about illustration and the origins of creativity featuring the work of 26 outstanding illustrators, along with in-depth interviews with each artist in which they discuss their ideas, inspirations and creative processes.